MANAGING IMPACT OF TIKTOK TO THE IT STUDENTS IN CEBU TECH UNIVERSITY -SAN FRANCISCO CAMPUS FOR AY 2022-2023 - Dr. Maria Cristina L. Nudalo-Gonzaga (EPRA International Journal of Economic Growth and Environmental Issues(EGEI), 2023)
TikTok is a powerful educational tool because it is both a learning platform and a social network. Users make new friends, scroll through the content, and discover new communities with like-minded people as they go. With 1.5 billion users, TikTok has surpassed more well-known social media platforms such as LinkedIn, Twitter, Pinterest, and Snapchat. The study focused on Cebu Technological University - San Francisco Campus hence, population consist of all the 261 full-time undergraduate BIT-CT students. The first come first serve basis technique was used to select the 50 sample respondents. A five-point Likert Scale rating was used to collect data from the participants. This was achieved as descriptive survey research design was adopted. The descriptive statistics of frequency counts and percentage, were used to analyze the demographic data while statistical treatment of Weighted Mean was used in testing the research questions. Research findings shows that great number of IT students in Cebu Technological University San Francisco, have agreed that TikTok has positive impact on their academic performance. To this end, the researchers recommended adding TikTok as one of the platforms for learning as well; Pre-recorded discussions should be non-lengthy and be done often as students find it more convenient this way; The researchers also recommend using educational instructions from TikTok as students thinks it’s reliable and relevant to their studies. Students should also be monitored by their parents on their Social Media consumption as five or more hours over the blue screen may implicate health problems. This rising platform is still pretty much unexplored and thus the researchers believes that further extensive studies from different area of concern should be studied.